PRAGMATIC CONTRAST AS A NEW WAY OF LEARNING (Konferensiyalar | Conferences, 2024)
Current parаdigms of language research characterized by anthropocentric and cross-disciplinary research. Since the early 1970s, language structural description has been used by speakers in intra and intercultural communication to conduct a multi-paradigm research on practical communication and to study the condition of linguistic means.